2004
DOI: 10.1111/j.1365-313x.2004.02101.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel anthocyanin malonyltransferase from scarlet sage (Salvia splendens) flowers: an enzyme that is phylogenetically separated from other anthocyanin acyltransferases

Abstract: SummaryAnthocyanin acyltransferases (AATs) catalyze a regiospeci®c acyl transfer from acyl-CoA to the glycosyl moiety of anthocyanins, thus playing an important role in¯ower coloration. The known AATs are subfamily members of an acyltransferase family, the BAHD family, which play important roles in secondary metabolism in plants. Here, we describe the puri®cation, characterization, and cDNA cloning of a novel anthocyanin malonyltransferase from scarlet sage (Salvia splendens)¯owers. The puri®ed enzyme (hereaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 22 publications
0
47
0
Order By: Relevance
“…Enzymes with HQT activity and showing a preference for quinate over shikimate as acyl acceptor cluster together in phylogenetic trees and are clearly distinct from HCT enzymes, which generally prefer shikimate to quinate as an acyl acceptor and are thought to work principally in lignin biosynthesis (Hoffmann et al, 2003(Hoffmann et al, , 2004Sullivan, 2009). This clear conservation of catalytic specificity within phylogenetically distinct clades of the BAHD family is surprising given that not all plant species accumulate caffeoylquinate; it might have been predicted that HQT activity would have evolved de novo in species that develop the ability to synthesize CGA, as reported for acylation of anthocyanins (Suzuki et al, 2004). Therefore, rather than being derived by convergence, the ability to synthesize caffeoyl or p-coumaroylquinate would appear to be an ancient function conserved in the HQT clade of proteins, which has been lost in some species, such as Arabidopsis (Niggeweg et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes with HQT activity and showing a preference for quinate over shikimate as acyl acceptor cluster together in phylogenetic trees and are clearly distinct from HCT enzymes, which generally prefer shikimate to quinate as an acyl acceptor and are thought to work principally in lignin biosynthesis (Hoffmann et al, 2003(Hoffmann et al, , 2004Sullivan, 2009). This clear conservation of catalytic specificity within phylogenetically distinct clades of the BAHD family is surprising given that not all plant species accumulate caffeoylquinate; it might have been predicted that HQT activity would have evolved de novo in species that develop the ability to synthesize CGA, as reported for acylation of anthocyanins (Suzuki et al, 2004). Therefore, rather than being derived by convergence, the ability to synthesize caffeoyl or p-coumaroylquinate would appear to be an ancient function conserved in the HQT clade of proteins, which has been lost in some species, such as Arabidopsis (Niggeweg et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The tree separated the proteins into five major clades (Fig. 3), with Vv3AT falling into clade IIIa (Tuominen et al, 2011), most similar to an anthocyanin acyltransferase, ANTHOCYANIN 5-O-GLUCOSIDE-4‴-O-MALONYLTRANSFERASE (Ss5MaT2), from Salvia splendens (Suzuki et al, 2004b). A nucleotide BLAST in the grapevine nucleotide database of the National Center for Biotechnology Information server revealed 10 related sequences ranging from 66% to 95% identity over 68% to 100% coverage of the Vv3AT coding sequence.…”
Section: Conserved Transcriptomic Changes In Transgenic Grapevines Wimentioning
confidence: 99%
“…When microarray techniques were used to analyze the transcriptomes of the transgenic berries, transcription of a gene putatively encoding for a member of the BAHD protein family correlated with the expression of VvMYBA. Members of the BAHD gene family encode acyltransferases that utilize CoA thioesters as their donor substrate both in planta (Fujiwara et al, 1998) and/or in vitro (Yonekura-Sakakibara et al, 2000;Yabuya et al, 2001;Suzuki et al, 2004b;D'Auria et al, 2007). Here, the characterization of the function of this BAHD gene from grapevine, identified through the microarray analysis of the transcriptome of berries with altered VvMYBA expression, is presented.…”
mentioning
confidence: 99%
“…For example, it has been shown that the most abundant anthocyanin in wild carrot (Daucus carota) is a sinapoylated cyanidin glycoside (Harborne et al, 1983;. The enzyme that catalyzes the sinapoylation of this anthocyanin uses sinapoyl-Glc as the activated sinapate donor Nakayama et al, 2003;Suzuki et al, 2004). As in Daucus, the major anthocyanin in Arabidopsis is acylated with a sinapoyl moiety (Bloor and Abrahams, 2002), which may be added by a sinapoyl-Glc-utilizing SCPL protein.…”
Section: Candidate Reactions For Scpl Acyltransferases Can Be Found Tmentioning
confidence: 99%